A multiscale study on the morphology and evolution of slip bands in a nickel-based superalloy during low cycle fatigue. (1st January 2020) - León-Cázares, F.D.; Schlütter, R.; Jackson, T.; Galindo-Nava, E.I.; Rae, C.M.F.
Graphical abstract: Abstract: Plastic deformation during low cycle fatigue in fcc materials with low stacking fault energy is accumulated in slip bands, which become preferential sites for crack initiation. Whilst these dislocation structures have been studied before, little has been done to assess the effect and evolution of the individual slip lines within them. In this study, samples of a γ ′ precipitate strengthened nickel-based superalloy are fatigued at room temperature and 700  ∘ C for 1, 40 and 500 cycles. The resulting dislocation structures are characterised via Electron Channeling Contrast Imaging and Transmission Electron Microscopy. We introduce a new methodology to measure slip band parameters such as the slip line spacing and shear step length by analysing the holes left by sheared precipitates in γ ′-etched secondary electron micrographs. Statistics of these parameters are obtained and compared for different conditions. Advantages of this technique include resolution at the scale of individual planes, acquisition of true three-dimensional data and applicability in the bulk of the material. The combination of these techniques provides a unique mechanistic and quantitative insight into the slip band and precipitate morphology evolution.